The management of regional soft tissue rheumatism disorders - Samborski, Włodzimierz (Przewodnik Lekarza/Guide for GPs, 2007)
The soft tissue rheumatism disorders are a group of diseases characterized by localized regional pain and lack of pathology in routine laboratory results. They can be divided into six main groups according to pain location and limitation of motion: enthesopathies, periarthropathies, tendovaginits, bursitis, fibromyalgia and other pain syndromes. In the management local injection of glicocortocoids with lidocain, analgesics, nonsteroidal anti-inflammatory drugs and myorelaxants are recommended, supported by physiotherapy methods. Patients with fibromyalgia need first of all novel antidepressants.